A risk-reward assessment of passing decisions: comparison between positional roles using tracking data from professional men`s soccer - Goes, F.; Schwarz, E.; Elferink-Gemser, M.; Lemmink, K.; Brink, M. (Science and Medicine in Football, 2022)
Introduction: Performance assessment in professional soccer often focusses on notational assessment like assists or pass accuracy. However, rather than statistics, performance is more about making the best possible tactical decision, in the context of aplayer`s positional role and the available options at the time. With the current paper, we aim to construct an improved model for the assessment of pass risk and reward across different positional roles, and validate that model by studying differences in decision-making between players with different positional roles. Methods: To achieve our aim, we collected position tracking data from an entire season of Dutch Eredivisie matches, containing 286.151 passes of 336 players. From that data, we derived several features on risk and reward, both for the pass that has been played, as well as for the pass options that were available at the time of passing. Results: Our findings indicate that we could adequately model risk and reward, outperforming previously published models, and that there were large differences in decision-making between players with different positional roles. Discussion: Our model can be used to assess player performance based on what could have happened, rather than solely based on what did happen in amatch.